2020
DOI: 10.1371/journal.pone.0234644
|View full text |Cite
|
Sign up to set email alerts
|

1024-pixel image matrix for chest CT – Impact on image quality of bronchial structures in phantoms and patients

Abstract: Objectives To compare objective and subjective image quality of bronchial structures between a 512pixel and a 1024-pixel image matrix for chest CT in phantoms and in patients. Materials and methods First, a two-size chest phantom was imaged at two radiation doses on a 192-slice CT scanner. Datasets were reconstructed with 512-, 768-, and 1024-pixel image matrices and a sharp reconstruction kernel (Bl64). Image sharpness and normalized noise power spectrum (nNPS) were quantified. Second, chest CT images of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Similar to Euler et al, we attribute this difference in the impression of image noise to the fact that if a soft kernel is used, this is the limiting factor for the resolution [ 22 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar to Euler et al, we attribute this difference in the impression of image noise to the fact that if a soft kernel is used, this is the limiting factor for the resolution [ 22 ].…”
Section: Discussionmentioning
confidence: 95%
“…Higher order bronchiole were detected in the middle lobe at a higher resolution but the image noise was roughly the same in both matrices. In another study by Euler et al, on the other hand, a hard kernel (Bl64) was used for a 512- and a 1024-pixel image matrix [ 22 ]. The results showed superior image sharpness and higher image noise for the 1024-pixel matrix and no difference in the subjective image quality or the depiction of bronchial structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study using the same CT platform as this study demonstrated that high matrix image reconstruction showed no significant difference in subjective evaluation of the bronchial tree but higher image sharpness and image noise compared to standard image reconstruction [ 23 ] In studies investigating CT scanners utilizing a combination of smaller detector size (0.25 × 0.25 mm) and high matrix image reconstruction, the technique was beneficial in lung nodule evaluation, [ 24 , 25 ] peripheral airway assessment, [ 26 ] small pulmonary ossification detection, [ 27 ] quantitative emphysema measurement, [ 28 ] automatic bronchial segmentation, [ 29 ] and virtual bronchoscopy. [ 30 ] Although smaller detector size exploits the advantage of high matrix image reconstruction, it is uncertain how high matrix image reconstruction improves the performance of other diagnostic tasks when combined with conventional CT detector size.…”
Section: Discussionmentioning
confidence: 99%